Youth development, vulnerability, : and the unspoken costs of renewable energy in rural South Africa - Rickerts, Caitlin (New Agenda: SA Journal of Social and Economic Policy, 2025)
This commentary draws on fieldwork conducted in a small Karoo town to explore how large-scale national renewable energy projects, which are lauded for providing much-needed socio-economic resources, can have unexpected and disruptive outcomes in the context of poverty, limited access to services, and social inequalities. CAITLIN RICKERTS focuses on the impact on young women and girls who, despite their agency, encounter new forms of vulnerability.